Rekonstruksi Sistem Peradilan Pidana Korupsi Dalam Rangka Menunjang Pembangunan Nasional - Maroni, Maroni; Fathonah, Rini; Ariani, Nenny Dwi; Anwar, Mashuril (Jurnal Hukum & Pembangunan, 2020)
The extent of the working area of the Regional District Court is equal to the provincial administration area consisting of Regency/city, while its position is in the provincial capital. This condition raises the legal gap in the eradication of corruption crimes, because on the one hand so the extent of the working area of the Court of Tipikor, causing many things corruption to be held, on the side will also require a large cost and a lot of judges power, and ideally will take a long time in the process of examination of a case. The study used qualitative research methods with normative and sociological juridical approaches.